Not all 3D‐printed bolus is created equal: Variation between 3D‐printed polylactic acid (PLA) bolus samples sourced from external manufacturers. Issue 3 (4th May 2022) - Brown, Kerryn; Kupfer, Tom; Harris, Benjamin; Penso, Sam; Khor, Richard; Moseshvili, Eka
Abstract: Introduction: Polylactic acid (PLA) is a promising material for customised bolus 3D‐printing in radiotherapy, however variations in printing techniques between external manufacturers could increase treatment uncertainties. This study aimed to assess consistency across various 3D‐printed PLA samples from different manufacturers. Methods: Sample prints of dimensions 5 × 5 × 1 cm with 100% infill were acquired from multiple commercial 3D‐printing services. All samples were CT scanned to determine average Hounsfield unit (HU) values and physical densities. The coefficient of equivalent thickness (CET) was obtained for both photons and electrons and dose attenuation compared to TPS calculations in Elekta Monaco v5.11. Results: Some samples showed warped edges up to 1.5 mm and extensive internal radiological defects only detectable with CT scanning. Physical densities ranged from 1.06 to 1.22 g cm −3 and HU values ranged from −5.1 to 221.0 HU. Measured CET values varied from 0.95 to 1.17 and TPS dose calculations were consistent with the variation in CET. Electron R50 and R90 shifted by up to 2 mm for every 1 cm of printed bolus, a clinically significant finding. Photon surface dose varied by up to 3%, while depth doses were within 1%. Conclusions: 3D‐printed PLA can have considerable variability in density, HU and CET values between samples and manufacturers. Centres looking to outsource 3D‐printed bolus would benefit from clear, open communication with manufacturers and undertake stringent QA examination prior to implementation into the clinical environment. Abstract : 3D‐printed polylactic acid (PLA) can have considerable variability in density, Hounsfield Unit (HU) and Coefficient of Equivalent Thickness (CET) values between samples and manufacturers. Multiple samples of dimensions 5x5x1 cm with 100% infill were assessed within this study. Centres looking to outsource 3D‐printed bolus would benefit from clear, open communication with manufacturers and undertake stringent QA examination prior to implementation into the clinical environment.